On the Skorokhod mapping for equations with reflection and possible jump-like exit from a boundary - Pilipenko, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
For a solution of a reflection problem on a half-line similar to the Skorokhod reflection problem but withpossible jump-like exit from zero, we obtain an explicit formula and study its properties.We also construct a Wiener process on a half-line with Wentzell boundary condition as a strong solutionof a certain stochastic differential equation.